Manajemen strategi pengembangan produk di asuransi syariah: tantangan dan peluang di pasar global - Faricha, Risalatul (Maliki Interdisciplinary Journal, 2025)
This article discusses the application of strategic management in product development for Islamic insurance amid global market challenges and opportunities. Using a conceptual-descriptive approach, it analyzes strategic management theories in relation to Sharia principles. Findings reveal that the main challenges of Islamic insurance include low public financial literacy, limited product innovation, and complex international regulations that are not fully aligned with Islamic law (OJK, 2023; Ahmed, 2016). Nevertheless, significant opportunities arise from service digitalization, cross-country collaboration, and the global awareness of ethical finance (EY, 2024). This study highlights the importance of adopting value-based and technology-driven strategies to create competitive, sustainable, and Sharia-compliant insurance products.